A simulation optimization method for vehicles dispatching among multiple container terminals. Issue 7 (1st May 2015) - Tao, Jinghui; Qiu, Yuzhuo
Highlights An online strategy with reduced empty traveling and global balancing is proposed. A linear evaluation function is established for real-time dispatching empty vehicles. Two berths model is established with ships arriving at different time. Different factors are introduced into the evaluation function by linear combination.